Application of the upgraded design of the STM32F103 battery monitoring system based on hospital power - Ni, Yujia; Xu, Cihai; Yang, Xiaodong; Gao, Chunhui (Heliyon, 2024)
This paper presents a battery monitoring system based on an STM32F103 microcontroller for hospital power applications. The system adopts a modular design to improve reliability and maintainability. It can monitor the terminal voltage and alternating current (AC) impedance of each battery in a battery pack with up to 128 cells, as well as the ambient temperature, relative humidity and hydrogen concentration. The device includes a keyboard for parameter input, a liquid crystal display (LCD) for information display, and multiple communication interfaces. The proposed solution can automatically monitor the battery voltage and AC impedance. It also provides alarms to greatly improve the stability of hospital power system operation and reduce the workload of maintenance personnel.